Feminisme liberal Air karya Djenar Maesa Ayu - Riska Lulu Hanifah; Alfandi Aditya Prayoga; Fina Setyaningrum; Wahyu Dini Septiari (Jurnal Komunitas Bahasa, 2023)
Very often differences occur in society, so there is no opportunity for women or men to change roles. Feminism is a movement for equality between men and women in the political, economic, educational, social fields, as well as organized activities that defend women's rights and interests. This research uses qualitative descriptive research. This research is important because of the swift social phenomena regarding gender equality in society, and as time goes on, there are still many discriminations against women and men, so education is needed so that people can equalize the rights of men and women.